Pelatihan Sustained Silent Reading (SSR) Untuk Guru di SDN Mekarwangi 1 dan 2 Kecamatan Saketi Kabupaten Pandeglang - Erna Irawati; Veny Agustini Prianggita; Nenden Suciyati Sartika; Susti Rahmah Yulita (Universitas Mathla'ul Anwar Banten, 2017)
SUSTAINED SILENT READING (SSR) TRAINING FOR TEACHERS IN SDN MEKARWANGI 1 AND 2 SAKETI DISTRICT PANDEGLANG REGENCY. Staff-training is one of eight principles that influences the success of Sustained Silent Reading (SSR) program. The eight principles of SSR program are access to book, book appeal, encourage to read, conducive environment, time to read, follow-up activity, non-accountability, and staff-training. This training facilitates the teachers in SDN Mekarwangi 1 and 2 to get the staff-training. The purpose of this training is to create an SSR program in those schools as a compulsory activity, read non-textbook reading for 15 minutes before class, which is obligated by government. Training was conducted a day in SDN Mekarwangi 1 and 2 through two steps: theoretical and practical material about SSR program. The result of the training is schools’ commitment and readiness to implement SSR program. SDN Mekarwangi 1 supported by school library is ready to implement SSR program next week after training, while SDN Mekarwangi 2 initiates One Student One Book movement to create class library before implementing SSR program. SSR activity in these two schools is adjusted to students’ condition thus in its implementation is combined with Read Aloud activity for lower class to keep motivation and the engagement of students’ reading activity in this SSR program.